Pengaruh Tekanan Waktu, Tindakan Supervisi dan Locus of Control Terhadap Penghentian Prematur Atas Prosedur Audit: Effect of Time Pressure, Supervision Measures and Locus of Control on Premature Termination of Audit Procedures - Rosdiana, Mega (Universitas Muhammadiyah Sidoarjo, 2017)
Premature sign off of audit procedure is one of those behaviors that can reduce audit quality. The present study was intended to examine whether time pressure, supervision, and locus of control affect the premature sign off of the audit procedure. The population used in this study is all auditors working at Public Accounting Firms in Surabaya. The data used is the primary data in the form of questionnaires distributed to the respondents. The sampling technique used is purposive sampling. The sample of research is 50 auditors from 17 Public Accounting Firms in Surabaya. Data analysis techniques used is multiple regressions. The results of this research showed that time pressure, supervision and locus of control affected the premature sign off of the audit procedures. The implication of this research result for the auditor is the higher the premature discontinuation of the audit procedure performed by the auditor will result in decreased audit quality and increased audit risk.